Avaliação da atenção concentrada e sustentada em motoristas idosos - Batista, Raquel Pinheiro (2022)
In the context of traffic, attention involves the selection of stimuli and the filtering of relevant and irrelevant information to direct internal actions and intentions to avoid involvement in accidents and drive the vehicle safely. Thus, the objective of this work was to review the constructs focused and sustained attention in elderly drivers and the possible relationship with license time and age. Two studies were carried out: Study 1 consisted of a literature review with the purpose of evaluating the constructs focused and sustained attention in elderly drivers. The results show the deterioration of attention with age, with difficulties in decision making and the need to build valid instruments that can evaluated the elderly driver, providing greater safety in the act of driving. Study 2 consisted of the application of the Focused Attention Test (TEACO-FF) and the Sustained Attention Test (AS) in elderly drivers. The scores on these tests varied, but did not significantly correlate with time of license and age. On the other hand, there was a significant correlation, of moderate magnitude, between the TEACO-FF and AS scores. Although the sample is small, this result suggests a possible overlap of functions designated as focused attention and sustained attention, a discussion that presents some controversies in the literature.